1997
DOI: 10.1115/1.2819499
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Control of Cloud Cavitation

Abstract: Generation mechanism of cloud cavitation on a hydrofoil section was investigated in a sequence of experiments through observation of cloud cavitation by high-speed video and high-speed photo as well as pressure measurements by pressure pick-ups and a hydrophone. The mechanism was also investigated by controlling cloud cavitation with an obstacle fitted on the foil surface. From the results of these experiments, it was found that the collapse of a sheet cavity is triggered by a re-entrant jet rushing from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
113
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(120 citation statements)
references
References 7 publications
6
113
1
Order By: Relevance
“…These profile and planform images are not unlike the descriptions of cloud cavitation in the two-dimensional hydrofoil experiments of de Lange et al (1994) Kawanami et al (1996). The most important difference in the present case is the substantial spanwise variation in the cavitation and its evoiution caused by the finite-span configuration of the hydrofoil.…”
Section: Stages Of the Cavitation Cyclementioning
confidence: 49%
See 2 more Smart Citations
“…These profile and planform images are not unlike the descriptions of cloud cavitation in the two-dimensional hydrofoil experiments of de Lange et al (1994) Kawanami et al (1996). The most important difference in the present case is the substantial spanwise variation in the cavitation and its evoiution caused by the finite-span configuration of the hydrofoil.…”
Section: Stages Of the Cavitation Cyclementioning
confidence: 49%
“…This re-entrant jet mechanism was described by Knapp (1955) Kawanami et al (1996). The re-entrant jet does not, however, progress uniformly toward the leading edge.…”
Section: Stages Of the Cavitation Cyclementioning
confidence: 89%
See 1 more Smart Citation
“…They showed that shed cloud is a large-scale vortex structure containing various small cavitation bubbles. Kawanami et al (1997) investigated the generation mechanism of cloud cavitation in details. Callenaere et al (2001) investigated the instability of a partial cavity induced by the development of a re-entrant jet using experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The role of surface condition has also been studied in a fully developed cavitating flow. Most of works about random distributed, transversal distributed, or local roughness show that it is possible to decrease sheet cavity length, in order to increase oscillation frequency of the cavity or even to change cavitation regime (Kawanami et al (1997); Stutz (2003); Coutier-Delgosha et al (2005); Yongjian et al (2009)). But, to the best of our knowledge, there is no study about the effect of organized longitudinal roughness like grooves on the cavitation regime.…”
Section: Introductionmentioning
confidence: 99%